2005
DOI: 10.1038/sj.cr.7290301
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CD13, CD107a, and CD164 as novel basophil-activation markers and dissection of two response patterns in time kinetics of IgE-dependent upregulation

Abstract: Using two-colour flow cytometry >200 antibodies submitted to the 8 th International Workshop of Human Leukocyte Differentiation Antigens (HLDA8) have been analyzed for their reactivity with resting and activated CD203c + basophils. Four antibodies either non-reactive or weakly reactive with resting basophils exhibited an increased reactivity with basophils activated by anti-IgE-mediated cross-linking of the high affinity IgE receptor (FcεRI). These include antibodies against CD164 (WS-80160, clone N6B6 and WS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
140
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(151 citation statements)
references
References 48 publications
8
140
1
2
Order By: Relevance
“…Two different histamine-containing compartments, which show distinct early signaling requirements and kinetics, have been described, namely, the CD203c compartment and the CD63 compartment. 2,3 The appearance of CD63 is invariably associated with AND. 2 Mechanisms that regulate basophil activation likely relate to activation conditions (IgE/FcεRI-dependent and -independent), mode of degranulation (piecemeal degranulation vs AND), and changes in functional properties of inhibitory receptors.…”
Section: To the Editormentioning
confidence: 99%
“…Two different histamine-containing compartments, which show distinct early signaling requirements and kinetics, have been described, namely, the CD203c compartment and the CD63 compartment. 2,3 The appearance of CD63 is invariably associated with AND. 2 Mechanisms that regulate basophil activation likely relate to activation conditions (IgE/FcεRI-dependent and -independent), mode of degranulation (piecemeal degranulation vs AND), and changes in functional properties of inhibitory receptors.…”
Section: To the Editormentioning
confidence: 99%
“…The surface markers CD203c and CD63 were studied as readouts for basophil activation since they have been reported that up-regulation of these two molecules follows two distinct pathways (23).…”
Section: Cd300a/c Engagement and Basophil Activationmentioning
confidence: 99%
“…This could be an important factor in the patients we studied as the presence of anti-gliadin IgG antibodies in 50% -60% of gluten-sensitive, IBS-like patients has been demonstrated [ 10 , 16 ] and we have demonstrated an evident overlap between patients " classified as gluten-sensitive " and those " classified as suffering from wheat hypersensitivity " [ 10 ]. Another factor which could negatively interfere with the accuracy of the new test is the reduced incubation time with the allergens, compared to the old test on separate leukocytes (15 min vs. 60 min) [ 17 ]. Finally, a direct comparison between the technique on whole blood and that on isolated leukocytes has been reported and the latter appeared to be more sensitive for allergen-induced basophil CD63 activation [ 18 ].…”
Section: Discussionmentioning
confidence: 94%